Why are shareholders not paid to give up their voting privileges? Unique evidence from Italy - Bigelli, Marco; Mehrotra, Vikas; Rau, P. Raghavendra (Journal of Corporate Finance, 2011)
Dual-class share unifications have typically been argued to be beneficial for voting shareholders, who are usually compensated for the loss of their superior voting privileges. However, no covenants exist that make this compensation mandatory for voting shareholders. In this paper, we examine a subset of dual class share unifications from Italy where, in the main, voting shareholders are not offered any compensation in lieu of the loss of their superior voting rights. We present a simple model describing the conditions under which the controlling voting shareholder will choose not to offer compensation to minority voting shareholders as part of a share unification. Our empirical results support the model predictions.